A tactical metabolic training model for collegiate basketball - Taylor, J. (Strength and Conditioning Journal, 2004)
Following is a review of research relevant to the physiological demands of basketball. A conceptual strength and conditioning model for the sport that integrates tactical metabolic training is also presented.